PENERAPAN STRATEGI PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KETERAMPILAN MENULIS DAFTAR PUSTAKA SISWA KELAS XI IPS II SMAK BONAVENTURA MADIUN TAHUN 2013−2014 - Amelda, Amelda; Adhani, Agnes (Educatio Vitae, 2015)
This research applies make a match learning strategy in order to increase the competence in writing bibliography for students 11th  grade IPX II SMAK Bonaventura Madiun 2013-2014. Make  a  match  learning  strategy  takes  a  role  in  improving  students’ liveliness and learning achievement. Therefore, this research purposes to improve the students’ liveliness and learning achievement in writing bibliography. This research is a class action, because the research data obtained based on learning activities on 23 November 2013 cycle I and cycle II December 5, 2013. The datum in cycle 1 retrieved based on the students’ liveliness, the score of the quiz, and the analysis of students’ learning achievement. Datum of the second cycle retrieved based on students’ performance, the score of make a match strategy, and the analysis of students learning achievement. Based on the result of this research, noted that make a match strategy can increase the liveliness of the students during the teaching and learning activities cycle I in high and medium activity 53.33%, whereas in cycle II the students’ liveliness in high and medium activity is 100% of 30 students and in cycle I students’  learning  achievement  in  writing  bibliography  the  percentages  are 53.33% or there are 16 students passes and 46.66% or 14 students fails, while on cycle II 100% or 30 students pass. The application of make a match strategies function to increase the learning process in the classroom, and be accepts by the reader.